Satisfaction Levels of Young Urban Residents With Public Sports Services in China During the COVID-19 Epidemic - Liu, Min; Yu, Dawei; Chen, Baoxia; Wu, Zhusheng; Chen, Zichao; Pan, Yuanfang; Gao, Shiying; Jia, Zexia; Li, Shanshan; Jiang, Yong (Frontiers in Psychology, 2022)
The extensive changes in public and private life caused by the ongoing COVID-19 epidemic in China have created a “new normal”. To understand urban residents’ satisfaction with public sports services under these conditions and to identify factors that influence satisfaction, urban residents in several major Chinese cities were randomly sampled with an online questionnaire to measure their level of satisfaction with public sports services in China during the COVID-19 epidemic. With the response rate of 87.9%, 703 valid questionnaires out of 800 questionnaires distributed were analyzed. A structural equation model was constructed where health literacy and the residents’ expectations were independent variables, residents' participation was a mediating variable, and residents' satisfaction was the dependent variable. Cronbach’s α test and Kaiser-Meyer-Olkin test confirmed that the questionnaire was reliable and valid. Survey results suggest that young urban residents' participation in public sports services is influenced by personal health literacy and residents' expectations. Participation serves a mediating role between health literacy and residents' satisfaction, but not between residents' expectations and their satisfaction. Young urban residents’ satisfaction with public sports services may be improved by increasing access to health information, improving hardware and software platforms to support those services, and catering the services to the interests of the population.